Challenging case of Whipple's disease: The contribution of radiology - João Garrido Santos, MD; Patrícia Costa, MD; António Galzerano, MD; Celso Matos, PhD; João Lourenço, MD (Radiology Case Reports, 2022)
Whipple's disease is a rare chronic infectious disease, caused by Tropheryma whipplei. The disease can be challenging to diagnose due to the variable clinical manifestations and the nonspecific laboratory and imaging findings. We report the case of a 75-year-old man, complaining of weight loss and arthralgias with an insidious onset. A thoracic, abdominal and pelvic CT was performed, demonstrating features suggestive of Whipple's disease. Although not specific, the imaging findings of fatty attenuation mesenteric and retroperitoneal enlarged lymph nodes are a common finding in Whipple's disease. Esophagogastroduodenoscopy with duodenal biopsy confirmed the diagnosis through PCR analysis.